ANALISIS SISTEM PENGELOLAAN SAMPAH PERKANTORAN KOTA PADANG MENGGUNAKAN METODE LIFE CYCLE ASSESSMENT - Rizki Aziz; Febriardy Febriardy (Jurnal Dampak, 2016)
Life Cycle Assessment (LCA)is a method to assess and to evaluate total environmental impact of a product, process or service. Simplified LCA has applied to solid waste management of institutional source of Padang City which applies two types of systems included Mixed Management System and Separated Management System. Study based on solid waste management of Major Office of Padang City which generated waste as 5.1194 m3 per week. Life cycle of mixed management system consist of generation, storage, collection, transportation to landfill, treatment on landfill, transportation to informal recycler, and treatment of informal recycler. Separated management system consist of generation, storage, collection, transportation to informal recycler, treatment on informal recycler, transportation to landfill, and treatment on landfill. Total material generated was 6.6320 m3 /weekon mixed system and 4.1815 m3/ weekon separated system. Energy needed for mixed system was 0.0164 m3/ weekand 0.0102 m3/ weekon separated system. The highest environmental impact for both systems were on ecosystem quality damage for treatment on landfill phase as 13.1519 weighting unit of mixed system and 7.7743 weighting unit for treatment on landfill for separated system. Comparative analysis of both systems on equal quantity of waste reveals that separated system is more environmentally friendly than mixed system. Keywords: Simplified LCA, solid waste management system of institutional source, mixed system, separated system, environmental impactpengolahan di lapak (lapak besar dan bandar), sedangkan untuk sistem terpisah terdiri dari tahap timbulan, tahap pewadahan, tahap pengumpulan, tahap pengangkutan ke lapak, tahap pengolahan di lapak (lapak kecil, lapak besar, dan Bandar), tahap pengangkutan ke TPA, dan tahap pengolahan di TPA. Total buangan material sebesar 6,6320 m3/mingguuntuk sistem tercampur dan 4,1815 m3/mingguuntuk sistem terpisah, volume energi yang dibutuhkan sistem tercampur yaitu 0,0164 m3/minggudan 0,0102 m3/mingguuntuk sistem terpisah. Dampak lingkungan terbesar yang mungkin terjadi adalah potensi gangguan keseimbangan ekologi, yaitu sebesar 13,1519 satuan bobot untuk pengolahan di TPA sistem tercampur dan 7,7743 satuan bobot untuk pengolahan di TPA sistem terpisah. Berdasarkan hasil analisis yang diperoleh, untuk sampah dengan kuantitas yang sama, sistem terpisah lebih ramah lingkungan dibandingkan sistem tercampur. Kata-kata kunci: LCA sederhana, sistem pengelolaan sampah perkantoran, sistem tercampur, sistem terpisah, dampak lingkungan